Leveraging internet use for sustainable agriculture: the impact of digital training on adoption of energy-smart agricultural practices and welfare - Ali Sher; Saman Mazhar; Dil Bahadur Rahut; Hongping Yuan (Scientific Reports)
Abstract This study examines the impact of digital training on the adoption of energy-smart agricultural (ESA) practices and farmers’ welfare using cross-sectional data from 723 households in Punjab-Pakistan. To address the potential endogeneity and selection bias, we use the endogenous switching regression (ESR) technique and introduce three valid, relevant, and robust instrument variables (IVs). Our results from the selection equation indicate that access to an internet connection, positive perceptions of internet information, social networks, gender (male), farm size, off-farm income, livestock holdings, and membership in farmer-based organizations (FBOs) are significantly associated with participation in digital training. The ESR estimates demonstrate that participation in digital training significantly influences productivity, adoption of ESA practices, and welfare. Specifically, farmers who engage in digital training experience an average increase in productivity of 55.21 kg per acre, an improvement in ESA practices adoption by 25.4%, and an increase in net farm returns by PKR14,365 per acre. The findings suggest several policy options to scale up the implementation of digital training for farmers to enhance the adoption of ESA practices and improve the welfare of rural communities. It provides cues on the role of prioritizing low-cost broadband connectivity in rural areas to bridge digital divides and integrate rural communities into sustainable supply chains.